2023
DOI: 10.1039/d3ee02010j
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up modification boosts the performance of narrow-bandgap lead–tin perovskite single-junction and tandem solar cells

Wenjun Zhang,
Lishuai Huang,
Hongling Guan
et al.

Abstract: GlyCl passivates the defects of narrow-bandgap Pb–Sn perovskites from bottom to up, boosting the solar cell efficiency from 14.28% to 22.07%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…4d, providing evidence of reduced current leakage and charge recombination. 55 The Mott–Schottky measurement (Fig. 4e) shows that the modified PSC exhibits a higher built-in potential ( V bi ) of 1.14 V than that of the control PSC (1.11 V), which is more favorable for the separation, transfer, and extraction of charges.…”
Section: Resultsmentioning
confidence: 97%
“…4d, providing evidence of reduced current leakage and charge recombination. 55 The Mott–Schottky measurement (Fig. 4e) shows that the modified PSC exhibits a higher built-in potential ( V bi ) of 1.14 V than that of the control PSC (1.11 V), which is more favorable for the separation, transfer, and extraction of charges.…”
Section: Resultsmentioning
confidence: 97%
“…The uniform distribution of surface contact potential is beneficial for effective carrier extraction and helps suppress non-radiative recombination, thus enabling the manufactured devices to have superior performance. [32] To gain insight into the effect of the SnC 2 O 4 modification on the photovoltaic performance, p-i-n planar PSCs with a configuration of ITO/PEDOT: PSS/perovskite/PCBM/BCP/Ag is fabricated and the schematic structure is shown in Figure 4a. Based on the J-V curve (Figure S12, Supporting Information) and the parameters summarized in Table S2 (Supporting Information), it is concluded that a 4% molar ratio of SnC 2 O 4 additive shows the best device performance, while an insufficient amount of SnC 2 O 4 additive cannot fully remove the residue on the grain boundary, thus resulting in limited improvement in device performance.…”
Section: Resultsmentioning
confidence: 99%
“…The uniform distribution of surface contact potential is beneficial for effective carrier extraction and helps suppress non‐radiative recombination, thus enabling the manufactured devices to have superior performance. [ 32 ]…”
Section: Resultsmentioning
confidence: 99%
“…The value of E F, edge was 1.08 eV for the control film and 0.87 eV for the OPC-modified film, while the corresponding E cutoff values were measured as 16.77 and 16.69 eV, respectively. By employing the equation E F = E cutoff – 21.22 eV, , the Fermi energy levels ( E F ) for the control and OPC-modified PVK films were calculated to be −4.45 and −4.53 eV, respectively. Furthermore, utilizing the formula E VB = E F – E F, edge , , the E VB values for the control and OPC-modified PVK films were computed as −5.53 and −5.40 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%